Factors Influencing Political Perspectives in a Changing Society: Case Study Bangkok, Thailand - Sipnarong Kanchanawongpaisan; Zhou Fei; Zheng Zeyu; Mcxin Tee; Liangyan Lu (International Journal of Computational and Experimental Science and Engineering, 2025)
This study investigates the behavioral and perceptual factors that influence the political perspectives of residents in Bangkok, Thailand. In an era of rapid digital transformation and evolving civic engagement, traditional demographic determinants of political orientation are being increasingly supplemented by dynamic influences, including media consumption, political participation, trust in information sources, and individual interest in politics. Employing a quantitative research design, data were collected from 400 respondents using a stratified random sampling technique across all 50 districts of Bangkok. A structured questionnaire was used to measure six key independent variables: political news consumption, political participation, trust in political information sources, perceived political efficacy, social media usage for political engagement, and interest in national politics. Multiple regression analysis was applied to examine the predictive power of these variables on political perspective. The results revealed that interest in national politics, political participation, trust in political information, and news consumption had a significant influence on political perspectives. At the same time, social media usage showed a marginal effect, and perceived efficacy had no significant impact. These findings suggest that in Bangkok's urban context, political attitudes are shaped more by active engagement and trust in information than by one’s self-perceived influence over political processes. The study contributes to the growing body of knowledge on political behavior in Southeast Asia, highlighting the importance of fostering credible information environments and participatory opportunities to support democratic development. Implications for civic education, media policy, and future research are also discussed.